If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5f + 4(-5 + 3f) = 1 + -1f 5f + (-5 * 4 + 3f * 4) = 1 + -1f 5f + (-20 + 12f) = 1 + -1f Reorder the terms: -20 + 5f + 12f = 1 + -1f Combine like terms: 5f + 12f = 17f -20 + 17f = 1 + -1f Solving -20 + 17f = 1 + -1f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add 'f' to each side of the equation. -20 + 17f + f = 1 + -1f + f Combine like terms: 17f + f = 18f -20 + 18f = 1 + -1f + f Combine like terms: -1f + f = 0 -20 + 18f = 1 + 0 -20 + 18f = 1 Add '20' to each side of the equation. -20 + 20 + 18f = 1 + 20 Combine like terms: -20 + 20 = 0 0 + 18f = 1 + 20 18f = 1 + 20 Combine like terms: 1 + 20 = 21 18f = 21 Divide each side by '18'. f = 1.166666667 Simplifying f = 1.166666667
| x+2+1=-4x | | -7x^2-40xy-25y^2=0 | | 40+.20x=60x | | 4x^2-20x+100=0 | | 4x^2-20x-100=0 | | x+2+1=-4 | | 3x^2+11xy-70y^2=0 | | F(x)=-4 | | 4(3b+a)= | | 2x+45+3x-20=180 | | x^2+16x+243=180 | | -2x=-35.24 | | 2x+4(y-3)=10y-8x | | 425=x+365 | | 13-x=36 | | x^3+21x+6=0 | | (ab+3a+7)-(-5ab-2)= | | x-y+2=1 | | 2y=10+4x | | -2y=3x-10 | | 5(3x-6)=4(10x+15) | | x^2+x-510=0 | | 3*x(x+3)=180*180 | | x-t+21=x-21-t | | 21-x=71-x | | x-21=x-71 | | log(X)=2.79 | | 2y-1y=0 | | XY(X^2+Y^2)=47.3 | | 300=100e^5x | | y=.50(6x-8) | | (8x+5)=13 |